fuzzy-dependent chance multi-objective programming for water resources planning of a coastal city under fuzzy environment - Peng, Hui; Zhou, Huicheng (Water and environment journal : WEJ, 2011)
A fuzzy multi-objective water resources management model is developed to determine the satisfactory water allocation plan in a coastal city of Northeast China. The imprecise predicted values of parameters are represented by fuzzy numbers, and seven fuzzy objectives of maximizing the possibilities of satisfying the water requirements for six users and total cost less than the expected value are considered. After weighted summation method (WSM) is used to transform the multi-objective model into a single-objective model, the satisfactory water allocation plan is efficiently derived according to decision makers' preferences by using a hybrid solution procedure of combining genetic algorithm with fuzzy simulation technique. Results of sensitivity test imply that the interval [0.2, 0.6] of cutting level, surface water and groundwater supplies have the most sensitive influence on results of the model. Moreover, results of discussion demonstrate that the assumption of linearity can be accepted, and membership function of fuzzy number has little influence on results of the model.